(3GeJMGf GdCdHG dcGaI GdCWHGs ((3eMeO Hf eMeO GdbhUhfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CeO HahGFO GdMce hCeG HYO aEf GdYdhe bO CTQbJ fjQGfgG hXgQJ HYO GdNehd BjGJgG s
(3BNQgG (B:s
(3GdSDGd GdYTQhf ce gi GdCSHGH ai bHhd GdYVh GdbGHd GdLhGH SHYJg afSCd Gddg GdYXje HdhZfG WGYJg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs